Omitting pulmonary radiotherapy in selected stage IV nephroblastoma patients with pulmonary metastases - van den Heuvel-Eibrink, M.M.; Gooskens, S.L.; Spreafico, F. (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2012)
The appropriate treatment approach of pulmonary metastases in children with nephroblastoma is controversial. One of the distinctions between the approaches lies in the indication of pulmonary radiotherapy. Some collaborative groups have advocated the routine use of pulmonary radiotherapy for metastases detected on conventional pulmonary X-ray, whereas other collaborative groups have adopted a strategy based on the response to a neoadjuvant three-drug regimen (1,2).